Unusual Presentation of Primary Sclerosing Cholangitis - BC Pineau; LP Pattee; S McGuire; A Sekar; LJ Scully (Canadian Journal of Gastroenterology)
A 23-year-old man presenting with acute pancreatitis and autoimmune hemolytic anemia was diagnosed with primary sclerosing cholangitis (PSC) without evidence of ulcerative colitis. This constellation of rare associations constitutes a unique mode of presentation of PSC. Within two years he also developed ankylosing spondylitis with sacroiliitis. Disordered immune regulation as a major factor in the mechanism of injury in PSC is supported by its increased association with other immunologically mediated disorders, most notably ulcerative colitis. Autoimmune hemolytic anemia, however, has been reported to be associated with PSC on only two occasions, and ankylosing spondylitis in the absence of ulcerative colitis is also unusual. In addition, the presentation of PSC with acute pancreatitis has rarely been described. This patient presented with several unusual features of PSC.